2010
DOI: 10.1111/j.1365-2222.2010.03482.x
|View full text |Cite
|
Sign up to set email alerts
|

Basophil activation test in the diagnosis of sulphite‐induced immediate urticaria

Abstract: We have read the interesting review on the clinical effects of sulphite additives recently published in the journal [1]. Sulphite hypersensitivity, particularly when manifesting mainly with cutaneous symptoms, remains a dark area of diagnosis where work-up and outcomes are frequently unclear. In this respect, here we describe a case that may help in the diagnostic work-up of patients claiming sulphite allergy.A 56-year-old non-smoking, non-asthmatic mechanic with no history of allergy, living in a vineyard are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Garcia-Ortega and his colleagues confirmed using the BAT that hypersensitivity to sodium metabisulfite induced CU [52]. Ebo et al reported the case of a patient who had a history of recurrent anaphylaxis after eating cheese, and found that hypersensitivity to the natural dye annatto (Ceska Annato WS E160b), which was positive on the BAT, was the cause of anaphylaxis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Ortega and his colleagues confirmed using the BAT that hypersensitivity to sodium metabisulfite induced CU [52]. Ebo et al reported the case of a patient who had a history of recurrent anaphylaxis after eating cheese, and found that hypersensitivity to the natural dye annatto (Ceska Annato WS E160b), which was positive on the BAT, was the cause of anaphylaxis [53].…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that urticarial symptoms were relatively more severe in the MBS PT (+) patients and lasted longer than in the rest. Similarly to other studies [7,11], we determined that the patients with sulfite contact allergies may also have shown symptoms after their ingestion and that patch tests may be useful to diagnose immediate reactions to sulfite-containing foods [7,20].…”
Section: Discussionmentioning
confidence: 96%
“…Several mechanisms are thought to play a role in the observed sulfites hypersensitivity, but IgE mediated reactions have rarely been documented so far [11,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] However, several studies had associated topical, oral, or parenteral exposure to high doses of sulfite with adverse reactions as dermatitis, urticaria, flushing, hypotension, abdominal pain, and diarrhoea. [2] In fact, several reports confirmed that some people can be extremely sensitive even to very low sulfite levels [3] and that bronchoconstriction can occur in many asthmatic patients [4] or in people exposed to high doses. [5] Exposure to high doses of sulfite can occur for consumption of food and drinks that contain this additive (as fruits, vegetables, salads, meat, gelatine, juices, vinegar, soft drinks, beer, wine, and others), through the use of several drugs (adrenaline, phenylephrine, corticosteroids, and local anaesthetics), some cosmetics (hair colors and bleaches, creams, and perfumes) or in some occupational settings (leather, textile, mineral, pulp, rubber, agriculture, and chemical industries).…”
mentioning
confidence: 99%